THE IMPACT OF GOLD PRICES PERCEPTION, KNOWLEDGE, PROMOTION, AND DIGITAL ACCESSIBILITY ON GENERATION Z INTEREST IN PEGADAIAN SYARIAH DIGITAL GOLD SAVINGS IN SEMARANG CITY - Rizky Ramadhani Syakur (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2026)
Advances in technology have given rise to innovations in digital finance, including digital gold savings. Although Generation Z is active in using technology, their participation in Pegadaian Syariah Digital Gold Savings remains low, with only 10% of customers under the age of 25 (CIF PT Pegadaian). This study aims to analyze the influence of gold prices, knowledge, promotion, and digital access convenience on Generation Z’s interest in this product. The research employed a quantitative method using primary data collected through questionnaires. The study population consisted of Generation Z in Semarang City who have an interest in digital gold savings products through the Pegadaian Syariah Digital platform, with a total of 100 respondents. Data analysis was conducted using SPSS 25 with multiple linear regression analysis. The results show that gold prices perception, knowledge, and digital access convenience have a positive and significant effect on Generation Z’s interest, whereas promotion has no significant effect. Simultaneously, all four variables were found to significantly influence Generation Z’s interest in Pegadaian Syariah Digital Gold Savings. These findings imply the importance of developing more targeted marketing strategies, enhancing financial literacy, and optimizing digital services in the Islamic finance sector. Furthermore, the results also contribute as a reference for future studies examining the investment behavior of young generations.Keywords: Gold Price Perceptions, Financial Knowledge, Promotion, Digital Accessibility, Pegadaian Syariah Digital